Detecting Secondary Caries Lesions: A Systematic Review and Meta-analysis - Brouwer, F; Askar, H; Paris, S; Schwendicke, F (Journal of dental research, 2016)
Secondary caries lesions are the main late complication of dental restorations, limiting their life span and generating costs by repeated reinterventions. Accurate detection of secondary lesions is crucial for estimating the true burden of the disease and allocating appropriate treatments. We aimed to assess the accuracy of detection methods for secondary caries lesions. Clinical or in vitro studies were included that investigated the accuracy of 5 detection methods--visual, tactile, radiography, laser fluorescence, quantitative light-induced fluorescence--of natural or artificially induced secondary lesions, as verified against an established reference test. Sensitivity, specificity, positive and negative likelihood ratios, as well as diagnostic odds ratios were calculated and publication bias assessed. From 1,179 screened studies, 23 were included. Most studies were performed in vitro, on permanent posterior teeth, and had high risk of bias or applicability concerns. Lesions were on proximal (14 studies) or other surfaces and adjacent to amalgam (16 studies) or tooth-colored materials. Visual (n = 11), radiographic (n = 13), and laser fluorescence detection (n = 8) had similar sensitivities (0.50 to 0.59) and specificities (0.78 to 0.83), with visual and laser fluorescence assessment being more accurate on nonproximal surfaces and adjacent to composites, respectively. Tactile assessment (n = 7) had low accuracy. Light-induced fluorescence (n = 3) was sensitive on nonproximal surfaces but had low specificities. Most analyses seemed to suffer from publication bias. Despite being a significant clinical and dental public health problem, detection of secondary caries lesions has been assessed by only a few studies with limited validity and applicability. Visual, radiographic and laser-fluorescence detection might be useful to detect secondary lesions. The validity of tactile assessment and quantitative light-induced fluorescence remains unclear at present.